Outcome of Renal Allograft Transplantation with Multiple Arteries - Mohammad Nazrul Islam; Mohammad Abdus Salam; Mohammed Rafiqul Islam; S M Yunus Ali; Md Nabid Alam; Md Saiful Islam (Bangladesh Journal of Urology, 2025)
Background: Anatomical variations of the grafts are one of the most difficult issues in renal transplantation. The most prevalent of these anatomical variants is thought to be multiple renal arteries (MRAs). Objective: To evaluate the short term outcome of renal allograft transplantation with multiple arteries. Methods: This quasi-experimental study was conducted in the Department of Urology, BMU, Dhaka, from December 2022 to November 2024. This study included 18 recipients who had living donor renal transplantation and received MRAs graft. The outcome variables were operation time, total ischemia time, length of hospital stay, post-operative complication and serum creatinine levels. All patients were followed up at the outpatient department initially once a week during the 1st months after discharged from hospital, then once a month for the following six months. Results: The median age of the patients was 40.0 years where 10 (55.6%) patients were female. The median operation time was 207.5 minutes. The median hospital stay of the patients was 18.5 days. In postoperative days, 2 (11.1%) patients had DGF and 1 (5.6%) patient had peri-transplant haematoma. None of them had acute tubular necrosis, renal artery stenosis and acute rejection. At baseline, the median serum creatinine level was 8.05 mg/dl which decreased to 1.49 mg/dl at 1st month. At the end of 6th month, the median serum creatinine level was 1.40 mg/dl. Conclusions: MRAs are safe for renal allograft transplantation, and recipients in need should not be denied grafts with multiple vessels. Bangladesh J. Urol. 2025; 28(1): 22-26